IMPLEMENTATION OF PROBLEM BASED LEARNING TO IMPROVE THE MATHEMATICAL LITERACY SKILLS OF GRADE VIII STUDENTS AT SMPN 6 WEST KARAWANG - Sonia, Yuni; Sopiany, Hanifah Nurus; Marlina, Rina (Journal of Authentic Research on Mathematics Education (JARME), 2026)
This study aims to improve students' mathematical literacy skills through the implementation of the Problem Based Learning (PBL) model for Grade VIII students at SMPN 6 Karawang Barat. The background of this research is based on Indonesia's low performance in mathematical literacy as reflected in the PISA survey results from 2000 to 2022, where Indonesia consistently ranked in the bottom ten globally. This research employs a quantitative method with a Pretest-Posttest Control Group Design. The population of the study consisted of all eighth-grade students, with two classes selected as samples: one as the experimental group receiving PBL instruction and the other as the control group receiving conventional instruction. The research instrument was a mathematical literacy test that had been validated for reliability. Data analysis techniques included descriptive statistics and inferential statistical tests. The results showed that there was a significantly higher improvement in the mathematical literacy skills of students in the experimental group compared to those in the control group. The experimental group showed an average gain of 33.21, while the control group showed an average gain of only 25.16. Therefore, the application of the PBL model proved to be more effective in enhancing students’ mathematical literacy skills compared to conventional learning models.